2010
DOI: 10.2298/jmmb1002131q
|View full text |Cite
|
Sign up to set email alerts
|

Interaction mechanism between refractory and melts in iron bath smelting reduction process

Abstract: The corrosion behavior of three sorts of refractories based on alumina-graphite were studied by immersion tests. The melts included smelting reduction molten slag and corresponding carbon saturated molten iron. The influence of test temperature, FeO content in slag and specimen rotative velocity on the corrosion rate of refractories was examined. By means of SEM and EDS, the microstructure change of the refractories after immersion test in kinds of melts was studied. The morphology of the deteriorated la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The polar group of hydroxamic acid is -CONHOH. Under alkaline conditions, the two oxygen atoms can undergo strong chelation with a metal ion on the mineral surface and form a stable five-membered ring [49][50][51] (Figure 8). At the same time, its nonpolar part may adsorb on the original absorbent monolayer via hydrogen bonding [51].…”
Section: Chelating Collectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polar group of hydroxamic acid is -CONHOH. Under alkaline conditions, the two oxygen atoms can undergo strong chelation with a metal ion on the mineral surface and form a stable five-membered ring [49][50][51] (Figure 8). At the same time, its nonpolar part may adsorb on the original absorbent monolayer via hydrogen bonding [51].…”
Section: Chelating Collectorsmentioning
confidence: 99%
“…Minerals 2023, 13, x FOR PEER REVIEW 8 of 34 its nonpolar part may adsorb on the original absorbent monolayer via hydrogen bonding [51]. Zhao et al conducted DFT analyses of cyclohexyl hydroxamic acid (CHA) and benzohydroxamic acid (BHA), which revealed that CHA has a higher HOMO energy, larger dipole moment, and more Mullikan or natural charges than BHA.…”
Section: Chelating Collectorsmentioning
confidence: 99%
“…Excepting for conventional production method, VAR [6,7], PAM [8,9], EBM [10][11][12], EBCHM [13], FFC based method comes into active using TiO 2 and Fe 2 O 3 mixture as electrolyte material with advantages of short procedure, low energy cost and small pollution [1,14]. There are some reports show ferrotitanium alloy can be produced by this method [1, 14,15,16,17,18,19,20], however, few study can be found about the formation mechanism of TiFe.…”
Section: Introductionmentioning
confidence: 99%